2007
DOI: 10.2298/bah0701383v
|View full text |Cite
|
Sign up to set email alerts
|

Infectious abortion in sheep

Abstract: Abstract:The abortions in sheep are important at various aspects, i.e. economical, animal healthcare or zoonotic. Abortions in sheep may occur sporadically or as enzootic outbreaks. The causative agent of the abortion is investigated if more than 2% of abortions in pregnant animals are registered within the herd. The amount of suspect material to be delivered for examination ranges from 12% to 21% of all registered abortions.Our research was carried out at the territory of AP of Vojvodina. Over a three-year-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Raorane et al, (2014) recorded 12% prevalence in clinic and farm environment and Soni et al, (2014) observed L. monocytogenes was also dominating close to the soil. Nightingale et al, (2004) put us a concern about dispersal of L. monocytogenes from farm environment and Vidic et al, (2007) confirmed the 1.2% positivity for the listeriosis. Silva et al, (2009) also confirm the presence of L. monocytogenes in cattle aborted fetus with 2.39%.…”
Section: Prevalence Of Lmonocytogenes From Bovine Environmentmentioning
confidence: 77%
“…Raorane et al, (2014) recorded 12% prevalence in clinic and farm environment and Soni et al, (2014) observed L. monocytogenes was also dominating close to the soil. Nightingale et al, (2004) put us a concern about dispersal of L. monocytogenes from farm environment and Vidic et al, (2007) confirmed the 1.2% positivity for the listeriosis. Silva et al, (2009) also confirm the presence of L. monocytogenes in cattle aborted fetus with 2.39%.…”
Section: Prevalence Of Lmonocytogenes From Bovine Environmentmentioning
confidence: 77%
“…Th e available data regarding Chlamydophila abortus infection on the territory of Serbia are relatively poor. Th e study covering the three-year-period reported the Chlamydophila abortus seroprevalence of 18.6% in 367 tested sera samples from sheep that have aborted (Vidić et al, 2007). Th e mentioned study was carried out on the territory of AP Vojvodina, in the north of the country.…”
Section: Resultsmentioning
confidence: 99%
“…These abortions develop as generalized infections symptomatically as a result of pathological changes depending on specific factors in placenta. These specific factors are bacteria, rickettsia, chlamydia, fungi, protozoan and viruses (Vidic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%